TRANSURETHRAL THULIUM:YAG LASER VAPOENUCLEATION IN BENIGN PROSTATIC HYPERPLASIA TREATMENT - Alexei Pleșacov (Arta Medica, 2021)
Objectives. The aim of the study was to analyze evidence based data from existing sources, regarding the role and the efficacy of transurethral Thulium:YAG laser vapoenucleation in benign prostatic hyperplasia treatment.